Cellulose and lignin biosynthesis is altered by ozone in wood of hybrid poplar (Populus tremula×alba) - Richet, Nicolas (Oxford University Press, 2011)
Wood formation in trees is a dynamic process that is strongly affected by environmental factors. However, the impact of ozone on wood is poorly documented. The objective of this study was to assess the effects of ozone on wood formation by focusing on the two major wood components, cellulose and lignin, and analysing any anatomical modifications. Young hybrid poplars (Populus tremula×alba) were cultivated under different ozone concentrations (50, 100, 200, and 300 nl l(−1)). As upright poplars usually develop tension wood in a non-set pattern, the trees were bent in order to induce tension wood formation on the upper side of the stem and normal or opposite wood on the lower side. Biosynthesis of cellulose and lignin (enzymes and RNA levels), together with cambial growth, decreased in response to ozone exposure. The cellulose to lignin ratio was reduced, suggesting that cellulose biosynthesis was more affected than that of lignin. Tension wood was generally more altered than opposite wood, especially at the anatomical level. Tension wood may be more susceptible to reduced carbon allocation to the stems under ozone exposure. These results suggested a coordinated regulation of cellulose and lignin deposition to sustain mechanical strength under ozone. The modifications of the cellulose to lignin ratio and wood anatomy could allow the tree to maintain radial growth while minimizing carbon cost.